The Impact of Tuberculosis Educational Program on Knowledge Among Nurses Working in Prison Clinics in Libya - Khadija Amer,; Muftah Elbahloul,; Sana Alghennai,; Sana Abuhajer, (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Nurses have become the key providers of healthcare in the prison setting in Libya, and those attending to tuberculosis patients face a high risk of infection themselves. The aim of this study was to assess the baseline knowledge of employed nurses at prison clinics about TB and to evaluate the impact of tuberculosis educational program on knowledge about tuberculosis. Methods. A sample of 102 nurses working at the six different prison clinics in Libya was used in the evaluation of this programme. At first, baseline knowledge was assessed using a validated self-administered pre-test questionnaire. The knowledge was assessed again at three weeks post-TB educational programme. Results. The overall baseline knowledge score on tuberculosis among the nurses was poor; only 32 (31.4%) of the nurses had a good level of knowledge. There was no significant association between the sociodemographic variables and knowledge level. A statistically significant improvement in knowledge was observed in the evaluation after the education programme (pre-test score =9.6±10, post-test score 25 ±8.51, P<0.001). The mean difference was 15.4 ±13.12 (95% CI 13, 18); however, the knowledge about tuberculosis of all the nurses was improved after the education programme. Conclusion. The health education intervention was effective in improving knowledge about tuberculosis among the nurses in the programme.